Involvement of the major glycoprotein (gp43) of Paracoccidioides brasiliensis in attachment to macrophages - Almeida, S. R. [UNESP]; Unterkircher, C. S.; Camargo, Z. P. (Oxford University Press (OUP), 1998)
The yeast form of Paracoccidioides brasiliensis, the causative agent of a deep mycosis in humans, is known to be phagocytized by, and to multiply inside, macrophages. In this work we describe the involvement of gp43, a major antigenic protein of P. brasiliensis, in the initial steps of attachment of the fungus to macrophages. Anti-gp43 F(ab) polyclonal fragments were capable of inhibiting phagocytosis in a concentrationdependent manner. Sheep red blood cells sensitized with purified gp43 were more endocytized than SRBC alone, and this process was also inhibited by anti-gp43 F(ab) fragments. Inhibition tests indicated the involvement of fucose and mannose residues in the phagocytosis of the fungus and of SRBC-gp43 by macrophages. Taken together, these results suggest that gp43 may be involved in the adherence and uptake of the fungus by murine peritoneal macrophages, and that this binding may be dependent on monosaccharide residues that are part of the gp43 glycoprotein. © 1998 ISHAM.
Keywords: Macrophages; Paracoccidioides brasiliensis; Paracoccidioidomycosis; Phagocytosis